Sikambang Art Pantun from the Barus Coast - Rahmad Fauzan As Meuraxa; Pujiati; Nursukma Suri; Rahimah (al-Afkar, Journal For Islamic Studies, 2025)
This article aims to discuss delves into the phenomenon of Sikambang pantun as a cultural heritage of coastal communities. This research aims to explore the characteristics, typology, and socio-cultural functions of Sikambang pantun within the context of life in Barus, Tapanuli Tengah, and Sibolga. By employing a historical research approach with systematic methodological stages comprising heuristic (source collection), source criticism, interpretation, and explanation this study identifies and analyzes various types of Sikambang pantun. The examined typology includes love pantun, advisory pantun, religious pantun, and other variations reflecting the richness of local cultural expression. Sikambang is far more than a traditional literary work; it serves as a significant medium of cultural communication within coastal societies. It functions as a channel for conveying life messages, a vessel for preserving traditional proverbs, a medium for documenting community narratives, an instrument of social communication, and a reflection of the lives and cultural identities of coastal communities. Its existence transcends mere poetic aesthetics, acting instead as a bridge connecting generations, transmitting noble values, and preserving local wisdom. This research provides meaningful academic contributions to understanding local cultural dynamics, particularly the literary expression of Sikambang pantun in the coastal regions of Barus, Tapanuli Tengah, and Sibolga. Through in-depth analysis, this study reveals the complexity and profound meanings embedded in each pantun, demonstrating that traditional literary art is not merely a relic of the past but a living document that continues to evolve and hold relevance.